PENGOLAHAN UBI JALAR PUTIH (lpomea batatas) DAN DAUNNYA DENGAN KOMBINASI KACANG KEDELAI (Glycine soja) MENJADI MI KERING SEBAGAI PANGAN TAMBAHAN BAGI IBU HAMIL - Saadah Hanim Parapat; Jumirah .; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Food diversification efforts can be done by making use of local food as diversity food. The programme of food diversification, need to be introduced such as processed yams and soy beans to get extra food such as new food alternative for pregnant women. Sweet potato and soy beans are potentially as a source of nutrients because it contains a number of macro-nutrients and micro nutrients. One of the preparations that can be made from yams and soy beans are dried noodles, so it can add to the diversity of dry noodles that had existed in the market. The purpose of this research is to know the nutrient content such as protein, iron, calcium and folic acid. This research is experimental research of dry noodle-making flour with the addition of a white Sweet Potato tubers and leaves with a combination of soy beans and wheat flour with a comparison of 60 gr + 20 gr + 25 gr + 15 gr. The results showed that the dry noodles flour white Sweet Potato tubers and leaves with a combination of soy beans have protein 1.00%, and iron 65,33 ppm, calcium 20.1 ppm and folic acid for pregnant women. It is advisable to society in order to make the addition of sweet potato tuber starch and leaves with a combination of soybeans as food supplement for pregnant women. Further research needs to be done also from dried noodle by using other local food. Keywords: Dried Noodles, The flour of Sweet potato tuber, The leaves of sweet potato, The flour of soy beans.